The Brécy depocenter as part of a new northern Massif Central Carboniferous–Permian Basin (France) - Beccaletto, Laurent; Bourquin, Sylvie (Comptes Rendus. Géoscience)
The reinterpretation of deep wells and the reprocessing and interpretation of 115 km of industrial seismic lines can be used to update the geometry, depositional environments and tectonic evolution of the Carboniferous–Permian Brécy depocenter (southwest Paris Basin). The present-day geometry of the Brécy depocenter is controlled by several eastward dipping normal faults, some of which possibly connected to deep detachments that were active during the late Carboniferous–Permian history. It is estimated that the maximum thickness of the Brécy depocenter is 3900 m. The filling provides evidence for a thick late Carboniferous–lower Permian syn-rift stage overlain by a thin post-rift stage, probably similar to the tectonic evolution of the northeastward basins in the Lorraine region of France and Germany and thus attributed to the lower-middle Permian. The facies generally characterize lake environments, with occurrences of sediment supply attributed to fluvial, alluvial fan and delta fan deposits. They mainly display a retrogradational–progradational pattern during the syn-rift stage, and a retrogradational pattern during the post-rift stage. The Brécy area was part of a larger late Variscan basin during the latest Carboniferous–early Permian times in the northern Massif Central region.